Gambaran Peran Keluarga Dalam Upaya Pencegahan Covid-19 Di Desa Batu Merah RT 006/RW 009 Tahun 2020 - Ira Sandi Tunny (Jurnal Anestesi, 2023)
Corona virus is a large family virus that causes illness ranging from mild to severe symptoms. Covid-19 is a new type of disease that has never been previously identified in humans, the virus that causes Covid-19 is called Sars-CoV-2. Corona viruses are zoonotic (transmitted between animals and humans). Until now there is no vaccine to prevent the corona virus, however, at least there are several ways that can be done to reduce this virus. The purpose of this study is to describe the role of the family in the prevention of COVID-19 in Batu Merah village RT 006 / RW 009 in 2020. The design of this study used a descriptive survey plan. The sampling technique used was proposive sampling. The variable in this study is a single variable. The instrument used in this study was a questionnaire. The number of samples in this study were 30 respondents. Of the 30 respondents studied, 17 respondents (56.7%) had good family roles, and 13 respondendents (43.3%) were not goot. The results of this study are that there is a major influence on the role of the family in handling Covid-19 in Batu Merah village RT 006 / RW 009 in 2020.